March1 E3 Ubiquitin Ligase Modulates Features of Allergic Asthma in an Ovalbumin-Induced Mouse Model of Lung Inflammation - Osama A. Kishta; Antoine Sabourin; Leora Simon; Toby McGovern; Maxime Raymond; Tristan Galbas; Abdelilah Majdoubi; Satoshi Ishido; James G. Martin; Jacques Thibodeau (Journal of Immunology Research)
Membrane-associated RING-CH-1 (March1) is a member of the March family of E3 ubiquitin ligases. March1 downregulates cell surface expression of MHC II and CD86 by targeting them to lysosomal degradation. Given the key roles of MHC class II and CD86 in T cell activation and to get further insights into the development of allergic inflammation, we asked whether March1 deficiency exacerbates or attenuates features of allergic asthma in mice. Herein, we used an acute model of allergy to compare the asthmatic phenotype of March1-deficient and -sufficient mice immunized with ovalbumin (OVA) and later challenged by intranasal instillation of OVA in the lungs. We found that eosinophilic inflammation in airways and lung tissue was similar between WT and March1−/− allergic mice, whereas neutrophilic inflammation was significant only in March1−/− mice. Airway hyperresponsiveness as well as levels of IFN-γ, IL-13, IL-6, and IL-10 was lower in the lungs of asthmatic March1−/− mice compared to WT, whereas lung levels of TNF-α, IL-4, and IL-5 were not significantly different. Interestingly, in the serum, levels of total and ova-specific IgE were reduced in March1-deficient mice as compared to WT mice. Taken together, our results demonstrate a role of March1 E3 ubiquitin ligase in modulating allergic responses.